Harnessing Biochar for Sustainable Horticulture: Strategies to Cope with Abiotic Stress - Matteo Lentini; Michele Ciriello; Youssef Rouphael; Emanuela Campana; Francesco Primo Vaccari; Stefania De Pascale (Horticulturae)
Biochar, an important by-product of the waste biomass pyrolysis process, shows great potential to reduce the environmental impact of and address the serious problems related to climate change as well as to define an efficient circular economy model. Its use as a soil conditioner has increased the interest in biochar in agriculture over time. This review investigates how critical aspects such as starting material, temperature, and the presence or absence of oxygen during the pyrolysis process influence the yield and quality of this valuable soil conditioner. Considering the horticultural sector, this review also provides a comprehensive and detailed overview of how biochar positively influences growth, development, and yield by explaining the mechanisms and modes of action under both optimal growth conditions and unfavorable contexts (salt and water stress and the presence of heavy metals). The main mechanisms highlighted by this literature review are improvement in soil aeration and water-holding capacity, microbial activity, and nutritional status of soil and plants, as well as alterations in some important soil chemical properties. This in-depth review of the literature highlights how the interaction between biochar types, dose, crop species, and growing conditions (optimal or nonoptimal) result in nonunique responses. The heterogeneity of the results reported in the literature confirms how many of the topics discussed deserve further investigation, with particular attention to identifying the right dose of biochar in relation to the different preharvest factors considered.